Photosensitive field emission study of SnS2 nanosheets (27th International Vacuum Nanoelectronics Conference ) - Joshi, Padmashree D.; Joag, Dilip S.; Rout, Chandra Shekhar; Late, Dattatray J. (2014 27TH International Vacuum Nanoelectronics Conference (IVNC), 2014)
SnS2 nanosheets (SnS(2)NSs), synthesized by one-step hydrothermal reaction, are subjected to Field Emission (FE) studies. For synthesis, specific concentrations of Na2SnO3 and thioamide solution are used. The FE study is carried out in all metal Ultra High Vacuum (UHV) chamber in planar diode configuration at a base pressure of similar to 10(-8) torr. A maximum current density of 110 mu A/cm(2) was attainable. The turn on field required to draw a current density of 1 mu A/cm(2) is found to be 2.6 V/mu m. A separate study was carried out to investigate the photosensitivity of the emitter by illuminating the specimen under visible light. In dark, the FN plot is non-linear, indicative of semiconductor nature of the emitter. However, on illumination, the FN plot is observed to be linear. This remarkable change can be explained by the photoconductivity imparted on illumination. The field at the tip is high in presence of light, than in dark, due to enhanced conductivity. It is also observed that on switching ON the light, the FE current increases almost instantaneously. Repetitive switching is observed at a fixed applied voltage, generating current pulses. The visible light soaking of the sample is carried out by illuminating the lamp for more than 100 minutes, where the current seems to saturate. On switching off the lamp the emission current decayed almost to its initial value exponentially. The photosensitivity has been studied for different wavelengths in the visible spectra. The maximum photosensitive field emission is observed for green filter. With this photoresponse, it is envisaged that SnS2 nanosheets are a potential candidate for optoelectronic applications of field emitters.
Keywords: field emission; photosensitivity; Photoswitching